David Rapaport papers - Rapaport, David; Strasser, Elvira Rapaport
Correspondence, memoranda, speeches, lectures, writings, reports, notes on dreams, transcripts of discussions and conference proceedings, biographical material, bibliographies, printed matter, and other papers concerning Rapaport's research and writings in the fields of psychology and psychoanalysis chiefly while a research associate at the Austen Riggs Center in Stockbridge, Mass. Documents his development of diagnostic psychological testing and his efforts to clarify and systematize psychoanalytic theory. Research topics also include consciousness, ego psychology, emotions and memory, metapsychology, motivation, and thought processes.
Papers of Rapaport's wife, Elvira Rapaport Strasser, consist of correspondence, her unpublished memoirs, and materials documenting programs and scholarships established in her husband's name. Subjects of Stasser's memoirs include her early life in Hungary and her experiences on a kibbutz in Palestine, 1933-1935.
Correspondents include Bruno Bettelheim, John C. Burnham, Sibylle K. Escalona, Hanna Fenichel, Anna Freud, Merton Max Gill, Heinz Hartmann, Lawrence S. Kubie, Martin Mayman, Karl A. Menninger, Roy Schafer, Richard F. Sterba, and Peter H. Wolff.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Psychologist and author. Born 1911; died 1960.
Collection material in English and Hungarian.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bettelheim, Bruno -- Correspondence; Burnham, John C. -- 1929- -- Correspondence; Escalona, Sibylle K. -- 1915- -- Correspondence; Fenichel, Hanna -- Correspondence; Freud, Anna, -- 1895-1982 -- Correspondence; Gill, Merton M. -- 1914-1994 -- Correspondence; Hartmann, Heinz, -- 1894-1970 -- Correspondence; Kubie, Lawrence S. -- 1896-1973 -- Correspondence; Mayman, Martin -- Correspondence; Menninger, Karl A. -- 1893-1990 -- Correspondence; Schafer, Roy -- Correspondence; Sterba, Richard F. -- Correspondence; Wolff, Peter H. -- Correspondence; Austen Riggs Center; Behaviorism (Psychology); Consciousness; Ego (Psychology); Emotions; Kibbutzim; Memory; Mental health facilities -- Massachusetts -- Stockbridge; Motivation (Psychology); Psychoanalysis; Psychological tests; Psychology; Spiritualism; Thought and thinking; Hungary -- Social life and customs; Palestine -- Social life and customs; Authors; Psychologists